616. Pharmacodynamics (PD) of the lipopeptide QPX9003 Against Acinetobacter baumannii and Pseudomonas aeruginosa in the Neutropenic Mouse Thigh Infection Model. (15th December 2022) - Tarazi, Ziad; Roos, Niki; Page, Ted; Li, Jian; Wang, Jiping; Roberts, Kade; Griffith, David
Abstract: Background: Acinetobacter baumannii and Pseudomonas aeruginosa are important pathogens in hospital-acquired infections and can be resistant to multiple classes of antibiotics. QPX9003 is a novel synthetic lipopeptide that is highly active in vitro against MDR Acinetobacter sp. and P. aeruginosa . The purpose of these studies was to determine the pharmacodynamic parameter that best described the bacterial killing of QPX9003 in vivo. PK-PD of QPX9003 against A. baumannii PK-PD of QPX9003 against P. aeruginosa Methods: Seven A. baumannii and six P. aeruginosa isolates were used in these studies. Swiss-Webster mice were rendered neutropenic by 150 mg/kg IP injections of cyclophosphamide 4 and 1 days prior to infection. The bacterial inoculum was prepared from an overnight culture adjusted to 10 8 CFU/mL then further diluted for inoculation into the thighs. Various dose and dose regimens of QPX9003 were administered by the IP route starting 2 hours post infection and continuing for 24 hours. Untreated control groups were sacrificed at the start of treatment. Treated and untreated control groups were sacrificed 24 hours after the start of treatment, thighs harvested, homogenized and plated to determine colony counts. PK was conducted in neutropenic, infected mice at doses ranging from 3 to 50 mg/kg administered by the IP route. The relationship between PK-PD parameters and the reduction in the log number of CFU per thigh between time zero and 24 h after the start of treatment were analyzed by using the sigmoid maximum reduction (Emax) PD model. Results: The activity of QPX9003 was best described by the 24h free AUC/MIC ratio, with stasis and 1 log kill targets of 47.1 and 67.1 for A. baumannii and 96.1 and 117 for P. aeruginosa, respectively. Organism MIC (mg/L) 24h Free AUC/MIC R 2 Stasis 1-log Kill A. baumannii (7 strains) 0.5 – 1 0.89 47.1 67.1 P. aeruginosa (6 strains) 0.5 – 2 0.94 96.1 117 Conclusion: The PD of QPX9003 was best described by the 24h free AUC/MIC ratio. Based on the QPX9003 MIC90 for P. aeruginosa (0.25 mg/L) and A. baumannii (1 mg/L), 24h free AUCs between 30 and 67 mg*h/L will produce 1-log of bacterial killing for ∼90% of P. aeruginosa and A. baumannii strains, respectively. QPX9003 is a potentially useful treatment for infections due to P. aeruginosa and A. baumannii, including MDR isolates, that is advancing in clinical studies. Disclosures: Ziad Tarazi, Qpex Biopharma: Employee Niki Roos, n/a, Qpex Biopharma: Employee Ted Page, n/a, Qpex Biopharma: Employee David Griffith, n/a, Qpex Biopharma: Employee.